Soybean Rust Resistance and Yield Performance of Elite Soybean Genotypes Across Diverse Environments in Uganda - Tonny Obua; Julius Pyton Sserumaga; Godfree Chigeza; Alex Malaala; Mercy Namara; Bruno Awio; Solomon Okello; Phinehas Tukamuhabwa (wiley, 2026)
ABSTRACT Soybean (Glycine max (L.) Merr.) is one of the important legumes globally, serving as an affordable and valuable protein source for humans and livestock. However, selecting the most suitable genotype across diverse environmental conditions remains a major challenge due to significant genotype‐by‐environment interactions (GEI). In addition, the quantitative inheritance of resistance to soybean rust and grain yield further complicates breeding efforts. This study aimed to assess the performance and stability of newly developed soybean genotypes regarding resistance to soybean rust and grain yield. Twenty‐two newly developed genotypes and two check varieties were evaluated using a randomized complete block design (RCBD) with three replications during five consecutive cropping seasons in six distinct locations in Uganda. GEI patterns were examined, and stable, high‐performing genotypes were found using genotype and genotype‐by‐environment (GGE) biplot analysis. The effects of genotype, environment, and genotype‐by‐environment interactions (GEI) on soybean rust resistance, hundred‐seed weight (HSW), and grain yield were all highly significant (p ≤ 0.01). The study revealed that genotypes 6N × SG‐P‐3‐2, 6N × SG‐P‐2, and 6N × SQ‐7 consistently performed better than all the other genotypes for soybean rust resistance, hundred seed weight, and grain yield across the six locations and five cropping seasons. Notably, these genotypes also demonstrated high stability for the three critical traits, making them strong candidates for varietal release. The results of this study provide valuable and new insights for soybean breeding programs in Uganda and the broader Sub‐Saharan Africa, offering a pathway for the development and release of rust‐resistant, high‐yielding soybean varieties adapted to varying agro‐ecological zones.